Electroacupuncture Ameliorates Acute Pancreatitis: A Role for the Vagus Nerve–Mediated Cholinergic Anti-Inflammatory Pathway - Zhang, Luyao; Wu, Zhiyang; Zhou, Jing; Lu, Shengfeng; Wang, Chaofan; Xia, Yiqiu; Ren, Hongyan; Tong, Zhihui; Ke, Lu; Li, Weiqin (Frontiers in Molecular Biosciences, 2021)
Organ failure brought by excessive inflammation is the leading cause of death in the early phase of acute pancreatitis (AP). Autonomic nervous system is one of the key pathways in the neuroimmune crosstalk and vagus nerve exerts anti-inflammatory effects through α7 nicotinic acetylcholine receptor (α7nAChR) signaling. Acupuncture has been widely used in traditional Asian medicine for the treatment of diverse disorders and recent studies suggested the inflammatory modulation effect of electroacupuncture (EA) might be mediated by autonomic nerve system. Here we investigate the therapeutic role of EA in AP. Two independent AP mouse models were used, caerulein hyperstimulation and pancreatic duct ligation. EA at Zusanli acupoint increased vagus nerve activity, suppressed systemic inflammation and alleviated the histopathological manifestations of pancreas. AP model induction resulted in a remarkable decrease in the frequency of α7nAchR+ macrophages in pancreas while EA counteracted this phenomenon. The anti-inflammatory, pancreatic protective and upregulation of α7nAchR effects of EA were abolished in mice with vagotomy. Also, the protective effect of EA in AP was attenuated in mice treated with mecamylamine, a nicotinic receptor antagonist. Taken together, EA could exert protective effects in AP and the mechanism may include exciting vagus nerve and activating cholinergic anti-inflammatory pathway.